The role of computed tomographic scan in ongoing triage of operative hepatic trauma: A Western Trauma Association multicenter retrospective study. Issue 6 (December 2015) - Kutcher, Matthew E.; Weis, Joshua J.; Siada, Sammy S.; Kaups, Krista L.; Kozar, Rosemary A.; Wawrose, Richard A.; Summers, Jessica I.; Eriksson, Evert A.; Leon, Stuart M.; Carrick, Matthew M.; Mallory, Gina; Sperry, Jason L.
Abstract : BACKGROUND: A subset of patients explored for abdominal injury have persistent hepatic bleeding on postoperative computed tomography (CT) and/or angiography, either not identified or not manageable at initial laparotomy. To identify patients at risk for ongoing hemorrhage and guide triage to angiography, we investigated the relationship of early postoperative CT scan with outcomes in operative hepatic trauma. METHODS: This is a retrospective review of 528 patients with hepatic injury taken to laparotomy without imaging within 6 hours of arrival to six trauma centers from 2007 to 2013, coordinated through the Western Trauma Association multicenter trials group. RESULTS: A total of 528 patients were identified, with a mean age of 31 years, 82% male, and 37% blunt injury; mean (SD) Injury Severity Score (ISS) was 27 (16) and base deficit was −9 (6); in-hospital mortality was 26%. Seventy-three patients died during initial exploration. Of 455 early survivors, 123 (27%) had a postoperative contrast CT scan within 24 hours of laparotomy. CT patients had more common blunt injury, higher ISS, and lower base deficit than those who did not undergo CT. CT identified hepatic contrast extravasation or pseudoaneurysm in 10 patients (8%). Hepatic bleeding on CT was 83% sensitive and 75% specific (likelihood ratio, 3.3) for later positive angiography; negative CT finding was 96% sensitive and 83% specific (likelihood ratio, 5.7) for later negative or not performed angiography. Despite occurring in a more severely injured cohort, performance of early postoperative CT was associated with reduced mortality (odds ratio, 0.16) in multivariate analysis. Blunt mechanism was also a multivariate predictor of mortality (odds ratio, 3.0). CONCLUSION: Early postoperative CT scan after laparotomy for hepatic trauma identifies clinically relevant ongoing bleeding and is sufficiently sensitive and specific to guide triage to angiography. Contrast CT should be considered in the management algorithm for hepatic trauma, particularly in the setting of blunt injury. Further study should identify optimal patient selection criteria and CT scan timing in this population. LEVEL OF EVIDENCE: Care management/therapeutic study, level IV; epidemiologic/prognostic study, level III.